A Survey of Factors Affecting Job Satisfaction among Employees: Exploring the Impact of Recognition, Advancement, Opportunity for Growth, and Responsibility on Job Satisfaction among Employees (Journal of Advances and Scholarly Researches in Allied Education, 2016)
There are various factors which affect the satisfaction of the employees working in an organisation. HR department is responsible for designing a policy which gives maximum satisfaction to the employees. In our study, we analysed the impact of four variables i.e. recognition, advancement, opportunity for growth and responsibility on 300 employees working in Delhi and NCR using One sample t-test. Our empirical results show that opportunity for growth is the foremost important variable, followed by recognition and advancement for the employees. However, the responsibility creates an adverse impact on the satisfaction of the employees.